2018
DOI: 10.1016/j.jcrc.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital frailty and hospital outcomes in adults with acute respiratory failure requiring mechanical ventilation

Abstract: PHF, identified by frailty diagnoses from before index hospitalization, may be a useful approach for identifying adults with ARF at increased risk of hospital mortality and pLOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…Initial analysis of 500 elderly patients identified eight variables significantly predictive of mortality including moderate-to-severe degrees of frailty, indicating that incorporating frailty into an ICU outcome model was appropriate – a result in agreement with much of the similar literature. 4,12,1719 Six of these variables already have a large evidence base indicating these would be expected to be significant predictors of mortality in our population. However, two parameters (the presence of any ECG abnormality and a hospital stay ≥5 days preceding admission) were novel, statistically significant indicators in predicting mortality in patients over 70 years of age in our ICU patient population.…”
Section: Discussionmentioning
confidence: 90%
“…Initial analysis of 500 elderly patients identified eight variables significantly predictive of mortality including moderate-to-severe degrees of frailty, indicating that incorporating frailty into an ICU outcome model was appropriate – a result in agreement with much of the similar literature. 4,12,1719 Six of these variables already have a large evidence base indicating these would be expected to be significant predictors of mortality in our population. However, two parameters (the presence of any ECG abnormality and a hospital stay ≥5 days preceding admission) were novel, statistically significant indicators in predicting mortality in patients over 70 years of age in our ICU patient population.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple comorbidities resulted in prolonged length of hospital stay. The previous studies have already reported that frailty and prolonged length of hospital stay in frail patients [ 11 , 21 , 22 ] are associated with poor long-term survival [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In traditional rescue protocols, the basic principle in traumatic shock is to facilitate fast anabiosis of patients through early and rapid venous replenishment of fluids so as to recover circulating blood volume, keep vital signs at a normal level to the maximum extent, and maintain hemoperfusion of important organs [7]. Relevant scholars have pointed out that supply of abundant blood, crystalloid solution, and other colloidal fluid is needed immediately in patients with hemorrhagic shock, and the total fluid infusion shall be 50%-100% higher than the blood loss volume [8].…”
Section: Discussionmentioning
confidence: 99%